PENDAPAT HUKUM TENTANG PEMBENTUKAN “KAMPUNG RESTORATIVE JUSTICE” DI KABUPATEN GRESIK - PARTIWI, FRIDA (Jurnal HUKUM BISNIS, 2026)
“Kampung Restorative Justice” is a community-based initiative aimed at resolving criminal cases through restorative justice principles that emphasize restoring relationships between offenders, victims, and the community. Unlike conventional approaches that focus mainly on punishment, this model prioritizes mediation, dialogue, and mutual agreement to achieve fair and balanced outcomes for all parties involved. The concept was developed to implement restorative justice at the village level, particularly in rural communities where social harmony and collective values play a significant role in maintaining order. In this approach, case resolution does not only impose sanctions on offenders but also seeks to repair the harm caused by the crime and rebuild trust among community members. Its main objectives include restoring damaged relationships, achieving peaceful settlements through agreements accepted by all parties, increasing public awareness about restorative justice, and preventing future crimes by encouraging offenders to take responsibility for their actions. The implementation generally involves mediation facilitated by community leaders, traditional authorities, or religious figures who act as neutral mediators. Community participation is essential, as residents may serve as witnesses or stakeholders in the reconciliation process. This model has been applied in resolving minor offenses such as petty theft and minor assault. However, challenges remain, including limited public understanding, differing views among law enforcement officials, and inadequate facilities to support mediation processes. Keyword: Restorative justice, Kampung Restorative Justice, community-based dispute resolution, mediation, criminal justice reform